2014
DOI: 10.1136/archdischild-2013-305799
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in the prevention of eczema: a randomised controlled trial

Abstract: ObjectiveTo evaluate a multistrain, high-dose probiotic in the prevention of eczema.DesignA randomised, double-blind, placebo-controlled, parallel group trial.SettingsAntenatal clinics, research clinic, children at home.PatientsPregnant women and their infants.InterventionsWomen from 36 weeks gestation and their infants to age 6 months received daily either the probiotic (Lactobacillus salivarius CUL61, Lactobacillus paracasei CUL08, Bifidobacterium animalis subspecies lactis CUL34 and Bifidobacterium bifidum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 38 publications
2
62
0
4
Order By: Relevance
“…At present, it is unclear whether faecal microbial diversity is related to differential dietary patterns, or whether these effects may interact in a manner that compounds disease risk. Results of intervention trials using probiotics to prevent allergy have been inconsistent, although a recent trial demonstrated a reduction in food sensitization with a multi-strain high-dose probiotic [37].…”
Section: Key Pointsmentioning
confidence: 98%
“…At present, it is unclear whether faecal microbial diversity is related to differential dietary patterns, or whether these effects may interact in a manner that compounds disease risk. Results of intervention trials using probiotics to prevent allergy have been inconsistent, although a recent trial demonstrated a reduction in food sensitization with a multi-strain high-dose probiotic [37].…”
Section: Key Pointsmentioning
confidence: 98%
“…Ostaje nedo voljno razjašnjeno što dovodi do takve predominacije Th2 limfocita 9 . Smatra se kako je poboljšanje higijenskih uvjeta, koje je dovelo do smanjene izloženosti mikroorganizmima tijekom ranog djetinjstva, zaslužno za ovakav trend porasta prevalencije 10,11 . Ova teorija poznata je kao higijenska hipoteza koju je 1989. godine postavio Strachan.…”
Section: Atopijske Bolesti -Globalna "Epidemija" Današnjiceunclassified
“…10 Danas je ona modificirana saznanjima o ulozi crijevne mikrobiote u sazrijevanju imunološkog sustava 12 . Komenzalne crijevne bakterije predstavljaju prvi i najveći izvor mikrobnog opterećenja i time inicijalni poticaj za uspostavu Th1/Th2 ravnoteže 4,9,11 .…”
Section: Atopijske Bolesti -Globalna "Epidemija" Današnjiceunclassified
See 2 more Smart Citations